Functional (psychogenic) movement disorders - Czarnecki, Kathrin (Curr Opin Neurol, 2012)
PURPOSE OF REVIEW: This review provides an overview of recent developments in diagnosis, pathophysiology, neuroimaging and management of functional (psychogenic) movement disorders (FMD) and highlights the current controversy on classification of somatoform disorders in the new DSM-5. RECENT FINDINGS: There has been increasing interest in recent years to study the underlying pathophysiology of FMDs, which has resulted in a broadened disease model, taking neurobiologic and psychosocial factors equally into account. In this context, the term “psychogenic” has been replaced by “functional” movement disorders by many authors in the field to express the changing focus towards a multifactorial disease model. The need for establishing a positive diagnosis of FMD as opposed to providing a diagnosis of exclusion is increasingly recognized and reflected by the introduction of “laboratory-supported” diagnostic criteria of FMD. Important advances have been made through behavioral, electrophysiological and neuroimaging studies although the fundamental etiology of FMD remains poorly understood. Of particular interest have been several reports on abnormal sensorimotor features and cortical inhibition in both organic and functional dystonia, highlighting possible shared traits of both conditions. In terms of treatment, recent studies have reported benefit from both psychiatric and physical therapy based interventions. SUMMARY: Increasing efforts have been made towards better understanding and treatment of FMD, and the disease model has been broadened to include neurobiologic and psychosocial factors. Laboratory-based diagnostic criteria have been established for many FMDs to support the clinical diagnosis. To determine the most effective management strategies for FMD, a closer collaboration between neurologists and psychiatrists and intensified research efforts with prospective treatment trials are needed.